2002
DOI: 10.1590/s0034-89102002000500008
|View full text |Cite
|
Sign up to set email alerts
|

Masculinidade e vulnerabilidade ao HIV de homens heterossexuais, São Paulo, SP

Abstract: OBJETIVO: Identificar aspectos da masculinidade relacionados à vulnerabilidade dos homens à infecção pelo HIV. MÉTODOS: Pesquisa qualitativa realizada com homens motoristas de ônibus e integrantes de uma Comissão Interna de Prevenção de Acidentes (Cipa) em uma empresa de transportes coletivos na cidade de São Paulo, SP. Foram gravadas e transcritas dez entrevistas individuais e quatro oficinas de sexo seguro. Seu conteúdo foi disposto e discutido em blocos temáticos relacionados à sexualidade, à infidelidade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
75

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 9 publications
2
18
0
75
Order By: Relevance
“…Other studies have also found an association between low socio-economic status and inconsistent condom use 20,21 . In a qualitative study with men without psychiatric disorders, one of the reasons for not using condoms was attributed to the high cost of this input 22 . Moreover, these findings suggest that men with low income may have the least information about forms of HIV transmission and low decision-making power within their relationships to practice safe sex 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found an association between low socio-economic status and inconsistent condom use 20,21 . In a qualitative study with men without psychiatric disorders, one of the reasons for not using condoms was attributed to the high cost of this input 22 . Moreover, these findings suggest that men with low income may have the least information about forms of HIV transmission and low decision-making power within their relationships to practice safe sex 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…None of them believed they could actually be infected; many had unprotected sex with their partners, and were prone to unwanted pregnancy and reinfection. Guerriero et al 6 pointed that feeling strong and immune to disease, engaging in impetuous risk behaviors, and believing that men needed sex more than women, were some aspects of masculinity associated with higher vulnerability to HIV among heterosexual men.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores apontam que a adesão ao modelo hegemônico está relacionada a um aumento de risco de doenças e dos índices de mortalidade masculina (COURTENAY, 2000;SABO, 2000;FRAGOSO;KASHUBECK, 2000;GUERRIERO;AYRES;HEARST, 2002). Em revisão da literatura sobre questões concernentes à saúde do homem norte-americano, Courtenay (2000) assinala que a adoção desse modelo está associada às três principais causas de morte em homens entre 15 e 35 anos: os ferimentos não intencionais, o homicídio e o suicídio.…”
unclassified